Peran Koperasi Pondok Pesantren (Kopontren) Jarinabi Mart dalam Meningkatkan Ekonomi Pondok Pesantren Jarinabi - Angga Ade Saputra; Daud - -; Sri - Kadarsih (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the role of the Jarinabi Mart Islamic Boarding School Cooperative (Kopontren) in improving the economy of the Jarinabi Rano Islamic Boarding School. Islamic boarding schools are educational institutions that also have the potential to develop the economy in their environment. The Jarinabi Mart Islamic Boarding School Cooperative was established as an effort to strengthen the economy of Islamic boarding schools and empower students and the surrounding community. The research method used is qualitative research with a case study approach. Data obtained through observation, interviews, and documentation. Respondents in this study were the management of the Jarinabi Mart Islamic Boarding School Cooperative, Islamic boarding school managers, and students. The results showed that the Jarinabi Mart Islamic Boarding School Cooperative had a significant role in improving the economy of the Jarinabi Rano Islamic Boarding School. This cooperative provides various consumption products to its members, including students and the surrounding community. The results showed that the Jarinabi Mart Islamic Boarding School Cooperative had a significant role in improving the economy of the Jarinabi Rano Islamic Boarding School. This cooperative provides various consumption products to its members, including students and the surrounding community.